Aplikasi Lapang Pupuk Hayati VP3 Dibandingkan Dengan Empat Macam Pupuk Hayati yang Beredar di Pasaran Terhadap Produksi Tanaman Kedelai (Glycine max L.) - Putri Nur Azizah; S Sunawan; Novi Arfarita (Universitas Islam Malang, 2021)
The study was undertaken to determine the effect of application VP3 biofertilizercompared to biofertilizers circulating in the market on the production of soybean (Glycinemax L.) in the field. The research was conducted on land in Bumi Asri Housing, DauDistrict, Malang Regency and the Applied Laboratory, Faculty of Agriculture, MalangIslamic University from June to October 2019. The research used a Randomized BlockDesign (RBD) with 6 treatments and was repeated 3 times. The results showed that theapplication of VP3 biofertilizer when compared with biofertilizers circulating in the marketin general gave better results to the growth and production variables of soybean in thefield. This was seen to be especially significant on the growth variable the leaf area perplant, total seed weight per plant, and total seed weight per plot.